HUBUNGAN ANTARA PRAKTIK ANTENATAL CARE PADA KEHAMILAN REMAJA DENGAN ANEMIA DI BOGOR - Koerniawati, Ratu Diah; Briawan, Dodik; Rimbawan, Rimbawan (Jurnal Gizi dan Pangan, 2016)
The objective of this research was to study antenatal care (ANC) practices and its association to anaemia on adolescent pregnancies. A cross-sectional design was applied in Bogor City between January to March 2016. A number of 72 pregnant adolescents (aged 10-19 years) participated in the study. Hemoglobin was collected through venous blood and analyzed with cyanmethemoglobin method. Data analysis using Chi-square test. The result showed that 30.6% of pregnant adolescent came lately for their first visit of antenatal care (missed first trimester). Overall, the prevalence of anaemia (Hb <11 g/dl) was found to be 45.8%. There was no significant association between anaemia with consumption of iron supplementation, energy intake, iron intake, and vitamin C intake (p>0.05). However, there was a significant association between protein intake and anaemia (p<0.05). Antenatal care pratices on adolescencts pregnancy was low. Many of them had anaemia in their pregnancy. Protein intake should be increased to reduce the incidence of anemia in adolescents pregnancy.Keywords: anaemia, antenatal care, pregnant adolescent